The Determinants of Debt and (Private-) Equity Financing in Young Innovative SMEs : Evidence from Germany - Volker Zimmermann; Axel Werwatz; Dorothea Schäfer (Deutsches Institut für Wirtschaftsforschung (DIW), 2004)
Financial theory creates a puzzle. Some authors argue that high-risk entrepreneurs choose debt contracts instead of equity contracts since risky but high returns are of relatively more value for a loan-financed firm. On the contrary, authors who focus explicitly on start-up finance predict that entrepreneurs are the more likely to seek equity-like venture capital contracts, the more risky their projects are. Our paper makes a first step to resolve this puzzle empirically. We present microeconometric evidence on the determinants of debt and equity financing in young and innovative SMEs. We pay special attention to the role of risk for the choice of the financing method. Since risk is not directly observable we use different indicators for financial and project risk. It turns out that our data generally confirms the hypothesis that the probability that a young high-tech firm receives equity financing is an increasing function of the financial risk. With regard to the intrinsic project risk, our results are less conclusive, as some of our indicators of a risky project are found to have a negative effect on the likelihood to be financed by private equity.
Keywords: G32; 330; Debt and equity financing; financial risk und project risk; venture capital and bank financing; Unternehmensgründung; Klein- und Mittelunternehmen; Finanzierung; Risiko; Fremdkapital; Risikokapital; Private Equity; Projektfinanzierung; Schätzung; Deutschland